Persepsi Pengguna TikTok terhadap Hubungan Lagu “You Will Be in My Heart” dengan Ayat Al-Qur'an pada Akun GITA - Arina Vionarsih; Rafli Ardiansyah; Rifki Rahman Ferdian; Tasya Nur Fadhilah; Dadan Firdaus (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study aims to analyze TikTok users' perceptions of the connection between the song "You Will Be in My Heart" and Quranic verses posted by the TikTok account @gitaasmaraa. This study used a descriptive qualitative approach, with Stuart Hall's encoding-decoding theory as the basis for the analysis. Data were obtained by observing the content, captions, and user comments on the posts. The results indicate that the connection between song lyrics and Quranic verses emerges through interpretation by both creators and audiences. Some song lyrics are understood to align with messages contained in the Quran, such as compassion, protection, closeness, and loyalty. Reception analysis revealed three forms of audience reception: dominant-hegemonic, negotiated, and oppositional. Most TikTok users accepted and supported interpretations linking song lyrics to religious values, while others viewed these connections as subjective and not directly related to the Quran. The results indicate that social media, particularly TikTok, serves as a communication space for negotiating meaning between popular culture and religious values. Thus, the meaning of digital content is not a singular entity, but rather is shaped through the interaction between creators and audiences in the ever-changing process of digital communication.